2021
DOI: 10.3390/medicina57101099
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium Difficile and COVID-19: General Data, Ribotype, Clinical Form, Treatment-Our Experience from the Largest Infectious Diseases Hospital in Western Romania

Abstract: Background and Objectives: In Coronavirus Disease 2019 (COVID-19), which is caused by the infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the clinical manifestations are primarily related to the pulmonary system. Under 10% of cases also develop gastrointestinal events such as diarrhea, nausea, vomiting and abdominal pain. Materials and Methods: We conducted an observational, retrospective study in the Infectious Diseases Clinic of ‘’Victor Babes’’ Hospital, Timis County, in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…Our results confirm the conclusions of many studies about an extremely high percentage of antibiotic use before the onset of CDI both during the pandemic and in the prepandemic period. The situation was similar in many other countries [6,17,31,32]. In the pandemic era, macrolides, third-generation cephalosporins, and quinolones were the most commonly prescribed antibiotics for the treatment of COVID-19 in our patients as empiric therapy for potential bacterial superinfection of the respiratory tract.…”
Section: Discussionsupporting
confidence: 65%
“…Our results confirm the conclusions of many studies about an extremely high percentage of antibiotic use before the onset of CDI both during the pandemic and in the prepandemic period. The situation was similar in many other countries [6,17,31,32]. In the pandemic era, macrolides, third-generation cephalosporins, and quinolones were the most commonly prescribed antibiotics for the treatment of COVID-19 in our patients as empiric therapy for potential bacterial superinfection of the respiratory tract.…”
Section: Discussionsupporting
confidence: 65%
“…As the HAI were not limited to pneumonia and bacteremia, the samples in which Clostridioides difficile toxins were detected (14.21%) should also be noted. In a study published by Marinescu et al and conducted in Timisoara, 23 it was found that 75% of COVID-positive patients who developed Clostridioides difficile were treated with antibiotics during the last 2 months. The destruction of the balance of the intestinal microbiota is inherent in the conditions of generalized antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since being firstly documented at the end of 2019, in Wuhan (China), the corona-virus disease 2019 (COVID-19), a zoonotic infection caused by the enveloped, positive-sense RNA single-stranded SARS-CoV-2, a novel member of the β-coronavirus genus, has spread rampantly, raising major public health concerns, and applying continuous strain on the global medical infrastructure. 9 , 10 SARS-CoV-2, initially thought to be limited to the respiratory tract, is now known to cause a diverse spectrum of clinical manifestations. 11 , 12 As more reports emerge in literature, it appears that glycoprotein spikes on the surface of SARS-CoV-2 engage angiotensin-converting enzyme-2 (ACE-2) receptors on respiratory epithelium, macrophages, and cardiac myocytes.…”
Section: Introductionmentioning
confidence: 99%